LCZ696 Ameliorates Oxidative Stress and Pressure Overload-Induced Pathological Cardiac Remodeling by Regulating the Sirt3/MnSOD Pathway. (18th September 2020) - Peng, Shi; Lu, Xiao-feng; Qi, Yi-ding; Li, Jing; Xu, Juan; Yuan, Tian-you; Wu, Xiao-yu; Ding, Yu; Li, Wen-hua; Zhou, Gen-qing; Wei, Yong; Li, Jun; et al.
Abstract : Aims . We aimed to investigate whether LCZ696 protects against pathological cardiac hypertrophy by regulating the Sirt3/MnSOD pathway. Methods . In vivo, we established a transverse aortic constriction animal model to establish pressure overload-induced heart failure. Subsequently, the mice were given LCZ696 by oral gavage for 4 weeks. After that, the mice underwent transthoracic echocardiography before they were sacrificed. In vitro, we introduced phenylephrine to prime neonatal rat cardiomyocytes and small-interfering RNA to knock down Sirt3 expression. Results . Pathological hypertrophic stimuli caused cardiac hypertrophy and fibrosis and reduced the expression levels of Sirt3 and MnSOD. LCZ696 alleviated the accumulation of oxidative reactive oxygen species (ROS) and cardiomyocyte apoptosis. Furthermore, Sirt3 deficiency abolished the protective effect of LCZ696 on cardiomyocyte hypertrophy, indicating that LCZ696 induced the upregulation of MnSOD and phosphorylation of AMPK through a Sirt3-dependent pathway. Conclusions . LCZ696 may mitigate myocardium oxidative stress and apoptosis in pressure overload-induced heart failure by regulating the Sirt3/MnSOD pathway.